2019
DOI: 10.1101/735357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Directed robust generation of functional retinal ganglion cells from Müller glia

Abstract: Glaucoma and optic neuropathies cause progressive and irreversible degeneration of retinal ganglion cells (RGCs) and the optic nerve and are currently without any effective treatment. Previous research into cell replacement therapy of these neurodegenerative diseases has been stalled due to the limited capability for grafted RGCs to integrate into the retina and project properly along the long visual pathway to reach their brain targets. In vivo RGC regeneration would be a promising alternative approach but ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Second, the newly generated neurons were reported to be morphologically, functionally, and molecularly indistinguishable from wild-type neurons in some studies (6-10) but abnormal and immature in others (3)(4)(5). Third, three studies reported that newly generated RGCs rapidly extended axons through the optic nerve to synapse on central targets and mediate visually evoked behaviors (7,8,10), despite the fact that regeneration of axotomized RGCs is highly inefficient in adult mammalian retina and the very limited number of regenerating axons seldom reach central targets (11).…”
Section: Interpreting Divergent Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the newly generated neurons were reported to be morphologically, functionally, and molecularly indistinguishable from wild-type neurons in some studies (6-10) but abnormal and immature in others (3)(4)(5). Third, three studies reported that newly generated RGCs rapidly extended axons through the optic nerve to synapse on central targets and mediate visually evoked behaviors (7,8,10), despite the fact that regeneration of axotomized RGCs is highly inefficient in adult mammalian retina and the very limited number of regenerating axons seldom reach central targets (11).…”
Section: Interpreting Divergent Resultsmentioning
confidence: 99%
“…Over the past few years, a flurry of studies has built on these findings, manipulating key regulators of gene expression to reprogram adult rodent MG (3-9), as well as amacrine cells (10), resulting in generation of functional retinal neurons. The experimental paradigm is similar in all cases: researchers use adeno-associated viruses (AAVs) as vectors with cell type-specific promoters (7)(8)(9) or Cre-expressing transgenic lines (3)(4)(5)10) to selectively target the cells to be reprogrammed. They then exploit this genetic access to introduce fluorescent reporters that track the cells and their progeny, along with interventions (overexpressed cDNAs, shRNAs, gRNAs, or conditional knockouts) to induce reprogramming (Figure 1).…”
Section: Preclinical Models Of Cell-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Neurod1-expressing amacrine and photoreceptor progenitors can be reprogrammed into RGCs when Atoh7 is inserted into the Neurod1 locus [ 64 ]. Xiao et al showed that combining Atho7 with Brn3b was able to reprogram mature mouse MG into RGCs efficiently and the MG-derived RGCs were functional, made appropriate central projections, and improved visual responses [ 119 ]. Ngn2 alone is also sufficient to lineage, reprogramming postnatal mouse MG into RGC-like neurons in vitro and inducing the generation of this neuronal type from late retinal progenitors in vivo [ 63 ].…”
Section: Rgc Regenerationmentioning
confidence: 99%
“…Strategies to reprogram existing cells to generate RGCs have been limited in mammalian retina, highlighting the need for innovative approaches. A preprint from Xiao et al (2019) have described the generation of induced RGCs from Müller glia in mice through the overexpression of Atoh7 and Pou4f2/Brn3b. These cells projected axons to superior targets in the brain and restored the vision in a disease model.…”
Section: Directed Strategies For Inducing Retinal Ganglion Cellsmentioning
confidence: 99%